2022
DOI: 10.2147/jir.s379093
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Neuroinflammation: A New Strategy for Treatment of Persistent Pain and Memory/Emotional Deficits in Chronic Pain

Abstract: Chronic pain, which affects around 1/3 of the world population and is often comorbid with memory deficit and mood depression, is a leading source of suffering and disability. Studies in past decades have shown that hyperexcitability of primary sensory neurons resulting from abnormal expression of ion channels and central sensitization mediated pathological synaptic plasticity, such as long-term potentiation in spinal dorsal horn, underlie the persistent pain. The memory/emotional deficits are associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 360 publications
0
5
0
Order By: Relevance
“…Emerging evidence has demonstrated that glial activation and overproduction of proin ammatory cytokines induce LTP and persistent pain [20]. In this study, we found that microglia were activated and proin ammatory cytokines IL-18 was upregulated in spinal cord after CCI surgery, which could be attenuated by perineural injection of BoNT/A.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Emerging evidence has demonstrated that glial activation and overproduction of proin ammatory cytokines induce LTP and persistent pain [20]. In this study, we found that microglia were activated and proin ammatory cytokines IL-18 was upregulated in spinal cord after CCI surgery, which could be attenuated by perineural injection of BoNT/A.…”
Section: Discussionmentioning
confidence: 53%
“…The central sensitization is underlined primarily by long-lasting enhancement of synaptic transmission, called long-term potentiation (LTP) [20]. Peripheral nerve injury can induce LTP and manifested as the increased amplitude of C-ber evoked eld potential in spinal dorsal horn.…”
Section: Perineural Injection Of Bont/a Attenuates CCI Induced Ltp An...mentioning
confidence: 99%
“…After activation, microglia further release pro-inflammatory factors, such as TNF-α and IL-1β. TNF-α aggravates the inflammatory response in AD [ 95 ] and disrupts the homeostasis of synaptic connections [ 96 ]. IL-1β can mediate the toxic effects of Aβ on synapses, causing changes in synaptic plasticity [ 97 ].…”
Section: Microglial Mechanisms Of Ad Pathogenesis and Memory Impairmentmentioning
confidence: 99%
“…In addition to its role in learning and memory, the hippocampus and/or amygdala may also play a role in chronic pain and be influenced by pain‐induced plasticity (McCarberg & Peppin, 2019 ). Inflammatory cytokines modulate synaptic plasticity in a region‐dependent manner, that is, enhancing synaptic connections in the dorsal horn of the spinal cord and reducing synaptic connections in the hippocampus, respectively, leading to persistent pain and memory/emotion deficits (Liu, 2022 ). Overproduction of pro‐inflammatory cytokines and glial cell activation impairs long‐term potentiation (LTP) in the hippocampus and reduces excitatory synapses in the hippocampus (Cowley et al., 2012 ; Pickering & O'Connor, 2007 ).…”
Section: Introductionmentioning
confidence: 99%